2022
DOI: 10.3390/ijerph19138077
|View full text |Cite
|
Sign up to set email alerts
|

Higher Neutrophil-To-Lymphocyte Ratio Was Associated with Increased Risk of Chronic Kidney Disease in Overweight/Obese but Not Normal-Weight Individuals

Abstract: Background: Inflammation has been proposed to play potential roles in the development and progression of chronic kidney disease (CKD). We evaluated the relationship of neutrophil-to-lymphocyte ratio (NLR), a systemic inflammation marker, with CKD in normal-weight and overweight/obese adults. Methods: This cross-sectional study included 2846 apparently healthy adults who underwent a health examination between August 2000 and April 2002. Normal weight was defined as a body mass index (BMI, kg/m2) of 18.5–24, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Second, though various criteria for diagnosis of PCOS have been proposed by different societies, including National Institutes of Health (NIH) in 1990, Rotterdam criteria in 2003, and Androgen Excess and PCOS Society (AE-PCOS) in 2006 [ 62 , 63 , 64 ], most of the cohort studies enrolled into this meta-analysis adopted Rotterdam criteria, and only one study conducted in 1992 using ultrasound image as diagnostic method was included [ 40 ]. Third, the definitions of BMI were heterogenous in the literatures [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Generally, studies conducted in western countries used WHO classification for nutritional status, whereas studies in China partly used WHO classification, partly used lower cutoff for overweightness and obesity (i.e., BMI 24 kg/m 2 and 28 kg/m 2 ) compared to the WHO classification.…”
Section: Discussionmentioning
confidence: 99%
“…Second, though various criteria for diagnosis of PCOS have been proposed by different societies, including National Institutes of Health (NIH) in 1990, Rotterdam criteria in 2003, and Androgen Excess and PCOS Society (AE-PCOS) in 2006 [ 62 , 63 , 64 ], most of the cohort studies enrolled into this meta-analysis adopted Rotterdam criteria, and only one study conducted in 1992 using ultrasound image as diagnostic method was included [ 40 ]. Third, the definitions of BMI were heterogenous in the literatures [ 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Generally, studies conducted in western countries used WHO classification for nutritional status, whereas studies in China partly used WHO classification, partly used lower cutoff for overweightness and obesity (i.e., BMI 24 kg/m 2 and 28 kg/m 2 ) compared to the WHO classification.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggested that NLR was associated with several comorbidities, including insulin resistance and CVD (31,32). Consistently, high levels of NLR were also determined to be related to the occurrence, and poor nutritional status as well as worse prognosis of CKD (33)(34)(35)(36)(37). Of note, Yoshitomi and colleagues observed that CKD patients with high NLR showed a nearly 1.7-fold increased risk for poor renal outcome when compared with the low NLR group in Japan (35).…”
Section: Discussionmentioning
confidence: 90%
“…This challenges the prevailing notion that CKD is predominantly linked to obesity. Some studies have shown that obesity is a significant risk factor for CKD development, independent of factors like type 2 diabetes mellitus and hypertension [ 31 ]. Another systematic review and meta-analysis showed that obese individuals have a 1.81 times higher risk of CKD [ 32 ].…”
Section: Discussionmentioning
confidence: 99%